SEMIOTIKA SAUSSUREAN DALAM THE CATCHER IN THE RYE: IDENTITAS REMAJA DI ERA DIGITAL - Huzairi, Ahmad; Manalu, Relly; Marisa, Dian; Pasaribu, Najmi Firdaus (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
D. Salinger’s The Catcher in the Rye (1951) remains one of the most discussed novels in modern American literature. This study analyzes key symbols in J. D. Salinger’s The Catcher in the Rye using Saussurean semiotics and connects them to teenage identity in the digital era. Each symbol’s meaning changes depending on Holden Caulfield’s emotions and situations, reflecting Saussure’s view that meaning is relational and context-dependent. Qualitative textual analysis is used to examine how the relationship between signifier and signified shifts across symbols such as the red hunting hat, the ducks in the lagoon, the Museum of Natural History, and the carousel. The findings reveal that Holden’s search for authenticity in a “phony” world mirrors how modern teenagers construct and negotiate their identities through digital signs like social media profiles and online expressions. This study fills a gap in previous scholarship by linking classical semiotics with contemporary youth culture by showing how meaning-making in both literature and digital life depends on interpretation, difference, and social context. Keywords: Saussurean semiotics, The Catcher in the Rye, teenage identity, digital era, symbolism.